Aleksandra Mężykowska, Establishment of the Registry of Damage – The first element in ensuring Russia’s financial accountability for the aggression against Ukraine, „European Society of International Law” 2023, vol. 12, no. 3 - Dąbrowska, Anna (Studia Prawa Publicznego, 2024)
Przegląd wybranych czasopism zagranicznych: Aleksandra Mężykowska, Establishment of the Registry of Damage – The first element in ensuring Russia’s financial accountability for the aggression against Ukraine (Utworzenie Rejestru Szkód – pierwszy element zapewnienia odpowiedzialności finansowej Rosji za agresję na Ukrainę), „European Society of International Law” 2023, vol. 12, no. 3, s. 1–10, https://esil-sedi.eu/esil-reflection-establishment-of-the-registry-of-damage-the-first-element-in-ensuring-russias-financial-accountability-for-the-aggression-against-ukraine/ (opr. Anna Dąbrowska)